Pengujian User Experience pada Aplikasi ITTP IGracias Menggunakan System Usability Scale (SUS) dan Usability Testing - Candra Haryanto, Erlan; Gustalika, Muhamad Azrino (Journal of Software Engineering and Multimedia (JASMED), 2023)
In the first time published, the IGracias ITTP android application has never experienced usability analysis testing of the application. Application analysis is a step to determine the successful implementation of an application. The purpose of this study is to determine the level of User Experience in the IGracias ITTP android application by implementing the Usability Testing and System Usability Scale (SUS) methods as an analysis of the usability of the IGracias ITTP android application. The research was conducted by utilizing the Maze and Google Form applications to collect questionnaire data. The results of the research on the reliability test showed that the Cronbach's α score was 0.818. Then in the Pearson Moment Product correlation validity test, it obtained a T-Table score of 1.734 which was stated as valid. Furthermore, the IGracias ITTP android application obtained a SUS score of 62. From the results of the SUS score, the IGracias ITTP android application was included in category D with the adjective Ok and for the results of Usability it obtained a score of 60.